Electro-optical effect and optical absorption in (K, Na)NbO3-based piezoceramics. (15th March 2020) - Sun, Haiqin; Jia, Qiannan; Li, Yong; Zhang, Qiwei; Hao, Xihong
Abstract: The intriguing coupling interactions between photochromism and ferroelectric polarization were firstly observed in Sm doped (K0.5 Na0.5 )NbO3 piezoceramics. After 407 nm irradiation, the maximum polarization ( P max ) and remanent polarization (Pr) intensities were dramatically decreased, whereas the coercive field, leakage current and photocurrent showed the remarkable increase. The variations of the polarization and photocurrent can be reversibly converted by alternating light irradiation and thermal stimulus, suggesting good polarization switching performance. This work provides a new route to effectively modulate ferro-/piezoelectric and photocurrent properties of ferroelectric materials by the non-contact remote control of light. Graphical abstract: (K, Na)NbO3 -based piezoceramics exhibited the photochromism-induced macroscopic polarization switching performance. Image, graphical abstract